Subfatin, Asprosin, Alamandine and Maresin-1 Inflammation Molecules in Cardiopulmonary Bypass - Hanbeyoglu, Onur; Aydin, Suna (Dove Medical Press Ltd, 2023)
Purpose: Cardiopulmonary bypass (CPB) is a nonphysiological procedure in which inflammatory reactions and oxidative stress are induced, hormones and hemodynamic parameters are affected, and circulation is maintained outside the body. This study aimed to examine the effects of CPB on blood subfatin (SUB), asprossin (ASP), alamandine (ALA) and maresin-1 (MaR-1) levels.Materials and Methods: Controls and patients who underwent open-heart surgery with CPB and whose age and body mass indices were compatible with each other were included in the study. Venous blood samples were collected from CPB patients (n =19) before anesthesia induction (T1), before CPB (T2), 5 min before cross-clamp removal (T3), 5 min after cross-clamp removal (T4), when taken to the intensive care unit (T5), postoperative 24th hour (T6) and 72nd hour (T7) postoperatively. Venous blood was collected from the healthy controls (n =19). The amounts of SUB, ASP, ALA, and MaR-1 in the blood samples were measured using an Enzyme-Linked Immunosorbent Assay (ELISA).Results: The amounts of SUB and MaR-1 in the control group were significantly higher than those in CPB patients, while these parameters in T1-T3 blood gradually decreased in CPB patients (p<0.01). It was also reported that the amounts of ASP and ALA in the control group were significantly lower than those in CPB patients, whereas those parameters in the T1-T3 blood samples increased gradually in CPB patients, but started to decrease in T4-T7 blood samples.Conclusion: These hormonal changes in the organism due to CPB demonstrate that hormonal metabolic adaptation mechanisms may be activated to eliminate the negative consequences of surgery. According to these data, SUB, MaR-1, anti-alamandine, and anti-asprosin could be used in CPB surgeries may come to the fore in the future to increase the safety of CPB surgeries.
Keywords: subfatin; maresin-1; asprosin; alamandine; cardiopulmonary bypass